2019
DOI: 10.1049/mnl.2018.5617
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of ZnO/SiO 2 nanocomposite from pomegranate seed extract: coating by natural xanthan polymer and its characterisations

Abstract: This work presents a simple, economical and, importantly, green process to develop a nanocomposite (NC) that covers the functions of surfactant and polymer flooding in enhancing oil recovery (EOR). Thus, xanthan coated ZnO/SiO 2 NC was prepared using the extract of the pomegranate seeds as a reducing and stabilising agent. The green synthesised NC was identified using the scanning electron microscopy, electron dispersive spectroscopy, elemental mapping, X-ray diffraction, and UV-vis analytical techniques. ZnO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The value of IFT decreased from 28.5 to 22 mN/m by adding 250 ppm of the synthesised NCs to the distilled water, which is considered as the minimum IFT obtained in this study. Then, IFT was increased with increasing the concentration of NCs to 500, 1000, 1500 and 2000 ppm; this is quite consistent with Eshraghi et al [39], and Ali et al [40, 41], where they only enabled to reduce the IFT to the optimum concentration of SiO 2 and then increased again with increasing the NPs concentration. The maximum IFT was measured between crude oil and NF2000 with 2000 ppm of CuO@Fe 3 O 4 @Xanthan NCs is 24 mN/m.…”
Section: Resultssupporting
confidence: 88%
“…The value of IFT decreased from 28.5 to 22 mN/m by adding 250 ppm of the synthesised NCs to the distilled water, which is considered as the minimum IFT obtained in this study. Then, IFT was increased with increasing the concentration of NCs to 500, 1000, 1500 and 2000 ppm; this is quite consistent with Eshraghi et al [39], and Ali et al [40, 41], where they only enabled to reduce the IFT to the optimum concentration of SiO 2 and then increased again with increasing the NPs concentration. The maximum IFT was measured between crude oil and NF2000 with 2000 ppm of CuO@Fe 3 O 4 @Xanthan NCs is 24 mN/m.…”
Section: Resultssupporting
confidence: 88%
“…The plant extracts as well as natural microbial strains secrete some chemicals which act as both reducing and capping agents [5]. Extracts of different plant parts have been utilised for the biosynthesis of ZnO NPs [6][7][8][9], but leaf extracts are more pronounced [6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported the presence of considerable antioxidants and bioactive phytochemicals such as phenolics, flavonoids, anthocyanidins and ascorbic acids inside the seed fractions of pomegranate [20,21]. In continuation of our previous researches on the green synthesis of NPs, in this study [22][23][24][25], the SiO 2 @ZnO@Xanthan NCs was green-synthesised using pomegranate seed extract as an efficient nano-adsorbent substrate for the filtration of water-based drilling mud.…”
Section: Introductionmentioning
confidence: 80%